Rechargeable Battery with DC-DC Boost Converter Powered by Solar based on P&O MPPT - Mohd Zamri, Nurul Arisya; Saiman, Suhaimi (Evolution in Electrical and Electronic Engineering, 2022)
This paper focuses on the employment of solar power as an influence supply in an exceedingly battery charging system. It becomes terribly tough for us to seek out a supply of power to charge the battery once running out of energy particularly being outside. As a result, charging the battery with a solar-powered device would be a lot of sensible. The system evaluates the management performance of the battery chargers in terms of voltage, current, and power output from solar energy. A 24V 12W solar battery is employed to power a battery that encompasses a 15Ah 24V charging output. This project methodology uses the MPPT boost device charge controller. However, this project uses perturb and observation methods to restore battery energy capability to most capability once recharged. as a result, it’s supposed to charge a 24V, 15AH lead-acid battery, it’s designed with 17V input voltage and 26.25V output voltage. The DC-DC boost device output voltage ought to be kept at 26.25V supported by the findings of the battery charging system simulation. to get a full charge, the battery needs 18000 seconds or five hours of charging time. For future work, the system is often achieved by performing MPPT using the Simulink model rather than putting code within the Embedded MATLAB operation or radiation and temperature are often provided as variable inputs within the Simulink model rather than constant values because of environmental changes.